THE ART OF PROMOTING AND MAINTAINING HEALTH AT WORK - A FUNDAMENTAL CONCEPT FOR OCCUPATIONAL PHYSICIANS - Brânduşa Constantin; Olga Odetta Duma (Romanian Society of Oral Rehabilitation, 2014)
Aim of the study To update one of the important tasks of the occupational physician - the preventive counseling of those involved in work system. Material and methods The study is an informational approach supported by a solid base of bibliographic data selected and presented by the authors in an explicit chronological arrangement regarding occupational medicine as preventive, but curative medical discipline too, and occupational physician's tasks in this field, mainly prophylactic. Results and discussion Pliny's, Hippocrates', Agricola' and Paracelsus' observations,harmoniously centralized by Ramazzini - father of occupational medicine, remain fundamental works over time and held the concept of work prevention; his work "Art of preserving the health of princes and senior persons" recorded valid principles of prevention, urgently needed today, also. Conclusions The occupational physicians should concentrate their activity on hazards and occupational diseases prevention, to be a diplomat actor on labor stage, advisor to employers and employees, skillful expert in the art of promoting health because of increased work productivity will result in personal satisfaction and material gain.